Proceedings of the Symposium on SDN Research 2016
DOI: 10.1145/2890955.2890960
|View full text |Cite
|
Sign up to set email alerts
|

Stitching Inter-Domain Paths over IXPs

Abstract: Modern Internet applications, from HD video-conferencing to health monitoring and remote control of power-plants, pose stringent demands on network latency, bandwidth and availability. Centralized inter-domain routing brokers is an approach to support such applications and provide inter-domain guarantees, enabling new avenues for innovation. These entities centralize routing control for missioncritical traffic across domains, working in parallel to BGP. In this work, we propose using IXPs as natural points for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…The work SDX [8] is deployed on Internet eXchange Points (IXPs) and impacts the interdomain traffic between the IXPs' member networks. The work CXP [10] further extends SDX. It uses SDN centralized control over multiple IXPs to create QoS-aware end-to-end paths.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The work SDX [8] is deployed on Internet eXchange Points (IXPs) and impacts the interdomain traffic between the IXPs' member networks. The work CXP [10] further extends SDX. It uses SDN centralized control over multiple IXPs to create QoS-aware end-to-end paths.…”
Section: Introductionmentioning
confidence: 78%
“…But it only impacts the inter-domain traffic between the IXPs' member networks. CXP [10] extends SDX to multiple IXPs' cooperation with centralized control to construct QoS-aware end-to-end paths across multiple ISPs. WEBridge [14] proposes an approach for inter-domain SDN to create peer session and exchange network views between SDN domains.…”
Section: Related Workmentioning
confidence: 99%
“…Future work : Close collaboration between the application and the network is effective for ultra‐low delay sensitive cases such as the NMP systems. The proposed Software‐Defined NMP solution can be also applied in the real Internet, considering the domains (Autonomous Systems) as “big switches” connected with physical links or classic overlay tunneling mechanisms –. Apart from this type of service, there are various daily life applications that can support this concept.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed Software-Defined NMP solution can be also applied in the real Internet, considering the domains (Autonomous Systems) as "big switches" connected with physical links or classic overlay tunneling mechanisms. [97][98][99] Apart from this type of service, there are various daily life applications that can support this concept. A modified version of our system could incorporate ultra-low delay encoding/decoding methods (eg, Opus 22 ) for modifying the audio bit-rate based on the network conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed solutions have demonstrated that bringing SDN to inter-domain routing can indeed improve the convergence performance of BGP [12], offer new routing capabilities [6], or lay the groundwork for new services and markets [13], [7]. However, most of previous works are systemoriented: they propose new systems or architectures, and focus on design or implementation aspects.…”
Section: Introductionmentioning
confidence: 99%